SnoopLigase catalyzes peptide-peptide locking and enables solid-phase conjugate isolation - Buldun, C; Jean, J; Bedford, M; Howarth, M (American Chemical Society, 2018)
Simple, efficient reactions for connecting biological building-blocks open up many new possibilities. Here we have designed SnoopLigase, a protein that catalyzes site-specific transamidation, forming an isopeptide bond with more than 95% efficiency between two peptide tags, SnoopTagJr and DogTag. We initially developed these components by three-part splitting of the Streptococcus pneumoniae adhesin RrgA. The units were then engineered, guided by structure, bioinformatic analysis of sequence homology, and computational prediction of stability. After engineering, SnoopLigase demonstrated high-yield coupling under a wide range of buffers and temperatures. SnoopTagJr and DogTag were functional at the N- or C-terminus, while DogTag was also functional at internal sites in proteins. Having directed reaction of SnoopTagJr and DogTag, SnoopLigase remained stably bound to the ligated product, thus reconstituting the parent domain. Separating products from unreacted starting material and catalyst is often as challenging as reactions themselves. However, solid-phase immobilization of SnoopLigase enabled the ligated SnoopTagJr–DogTag product to be eluted with high purity, free from SnoopLigase or unligated substrates. The solid-phase catalyst could then be reused multiple times. In search of a generic route to improve the resilience of enzymes, we fused SnoopTagJr to the N-terminus and DogTag to the C-terminus of model enzymes, allowing cyclization via SnoopLigase. While wild-type phytase and β-lactamase irreversibly aggregated upon heating, cyclization using SnoopLigase conferred exceptional thermoresilience, with both enzymes retaining solubility and activity following heat treatment up to 100 °C. SnoopLigase should create new opportunities for conjugation and nanoassembly, while illustrating how to harness product inhibition and extend catalyst utility.